Assessment of biofilm morphology upon exposure to biodegradable nanopolymers. - Tan, Jane Yi Lin. (2009)
Pseudomonas aeruginosa and Escherichia coli are able to form bacteria biofilms in the human body and on external surfaces, potentially leading to harmful infections that are difficult to eradicate. Bacteria biofilm has been shown to possess greater resistance against most antimicrobial strategies available. One objective of this project was to study how biofilm growth is affected by varying conditions of incubation time, incubation temperature and growth medium. One strain of P. aeruginosa and E. coli was each grown in nutrient medium (Luria-Bertani Broth) and minimal medium (M9 minimal medium) at 21°C, 30°C and 37°C for 24h, 48h and 72h in polystyrene wells of the Calgary Biofilm Device. Biofilm formation was indirectly quantified by staining with 0.005% crystal violet and measuring the crystal violet absorbance using destaining solution. Results showed that there was an optimal point in which the individual bacteria biofilm grew the best, and any deviation from this point produced far less amount of biofilm. Both bacteria showed optimal growth under LB Broth, although their optimal incubation times and temperatures differed. These differences may be explained by the complex mechanisms and synergistic effects taking place during biofilm formation and the different physiological characteristics of both bacteria. Results of the microtiter plate biofilm assay were used in the second objective of the experiment, which was to assess the morphology of biofilm upon exposure to biodegradable nanopolymers loaded with drug. The optimal amount of biofilm was first grown on pegs of the CBD and exposed to PLGA and PCL loaded with drug for 24h. The pegs were detached using sterilized pliers and mounted onto a scanning electron microscope for qualitative analysis of the biofilm morphology. Images from the SEM showed that PCL tagged with drug did possess the ability to target bacteria cells in biofilm, as seen from the reduced amount of slime. PLGA, on the other hand, did not show significant improvement in targeting the cells. The presence of PCL improved the targeting of bacteria cells as compared to using free drug alone. This may imply that the use of nanopolymers as drug carriers have potentially significant benefits in the medical and pharmaceutical industry, and drugs that have shown poor performance may be conjugated with nanopolymers to aid in their therapeutic effect in the human body.